The pandemic impact of COVID 19 on orthodontic practice: A cross sectional study - Muralidharan Dhanasekaran; I Bevin Shaga; Harish Ponniah; Padmasree Sankaranarayanan; Nagappan Nagappan; T M Parameswaran (Wolters Kluwer Medknow Publications, 2021)
Aim: The objective of this study was to determine the problem encountered by an orthodontist due to suspended treatment during and after lockdown COVID 19 and to assess the pandemic impact on orthodontic practices. Materials and Methods: This was a cross-sectional web-based questionnaire survey conducted among orthodontist in India. The pilot study was conducted to estimate the sample size and final sample size is 263 participants. The predesigned and validated, self-administered, structured 10 questions related to the impact of an orthodontist and their orthodontic practices during and after COVID 19 are used. The statistical analysis was done using Statistical Package for Social Sciences SPSS (V 22.0) the frequency distribution was computed. Results: The result showed that 81% orthodontist were reported that routine orthodontic treatment was disturbed due to this COVID 19 lockdown, about 79.1% reported hospital/clinic was closed due to lockdown with a duration of more than 1 month. Still, 64.6% orthodontist handling their orthodontic emergencies through telecommunication and 47.9% of orthodontist received a complaint about fixed appliance among all other appliances. Due to the current situation, 41.4% orthodontist suggested 3-6 months' period required to normalize the current situation and 66.9% agreed that there will be decline in orthodontic treatment need after COVID 19. Conclusion: Owing to the high virulence activity, elective procedures have been postponed and can manage a patient through virtual teleconsultation. Reassurance of the patient is needed regarding prolonged treatment duration due to this COVID 19 pandemic.